2021
DOI: 10.3389/fpls.2021.731079
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Quantitative Trait Loci Controlling the Development of Prickles in Eggplant by Genome Re-sequencing Analysis

Abstract: Eggplant (Solanum melongena L.) is the third most important crop in the family of Solanaceae. Prickles are considered as the undesirable traits during the plantation of eggplant and the transportation of fruits. In this study, we constructed a high-quality genetic linkage Bin map derived from the re-sequencing analysis on a cross of a prickly wild landrace, 17C01, and a cultivated variety, 17C02. The major quantitative trait locus (QTL) controlling the development of prickles on the calyx (explained 30.42% of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The Illumina HiSeq platform was used to re-sequence the whole genome of the two parents and 100 randomly F2 individuals, and the data and the map have been published in previous research papers ( Qian et al, 2021 ). A total of 278,891 bin markers containing 1,883,288 SNPs were obtained on 12 chromosomes.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Illumina HiSeq platform was used to re-sequence the whole genome of the two parents and 100 randomly F2 individuals, and the data and the map have been published in previous research papers ( Qian et al, 2021 ). A total of 278,891 bin markers containing 1,883,288 SNPs were obtained on 12 chromosomes.…”
Section: Resultsmentioning
confidence: 99%
“…The research team constructed a genetic linkage map by using the two parents and 100 randomly selected F2 individuals ( Qian et al, 2021 ). Biomarker Technology Co., Ltd. ( http://www.biomarker.com.cn/ ) completed the resequencing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in terms of transcriptional regulation, some glandular development regulators, such as members of the MBW complex and TTG2, were found to be differentially expressed in prickly and prickleless cultivars (Feng et al, 2015;Swarnkar et al, 2021;Pandey et al, 2018;Khadgi and Weber, 2020b;Saint-Oyant et al, 2018). Recently, a candidate gene controlling prickles number in eggplant organs, SmWOX3, has been fine mapped (Qian et al, 2021). In rice, its homologous gene OsGLR1 (WOX) controlled trichome initiation, as well (Li et al, 2012).…”
Section: Old Opinion New Perspectivementioning
confidence: 99%
“…In the past 20 years, scientists have detected many QTLs associated with the prick traits (leaf prickle, stem prickle, calyx prickle, and petiole prickle) on chromosomes 1, 2, 3, 5, 6, 7, 8, 9, and 12 by constructing the interspecific and intraspecific hybrid F2 populations. It was found that one prickle trait could be regulated by multiple QTLs, and some QTLs could regulate more than one prickle trait (Wei et al, 2020b;Doganlar et al, 2002;Qian et al, 2021;Portis et al, 2014Portis et al, , 2015Frary et al, 2014). Among the many QTLs, one hotspot QTL located on chromosome 6 was found to be associated with all prickle traits (Frary et al, 2014).…”
Section: Introductionmentioning
confidence: 99%